Disability Culture and the ADA - Brown, Steven E. (Disability Studies Quarterly, 2015)
This article begins with a personal, pre-Americans with Disabilities Act (ADA) story of employment discrimination and how from it I became involved with the Disability Rights Movement. The narrative then moves into my finding, exploring and discussing the importance of Disability Culture. Finally, thoughts are shared about the intersection of Disability Culture with the ADA.